2012
DOI: 10.1088/0954-3899/39/10/105106
|View full text |Cite
|
Sign up to set email alerts
|

On the possibility of enhanced fission stability for broken-pair excitations

Abstract: The fission of high-K, two-quasiparticle isomers is considered, with specific reference to 250 No, 254 No, and 256 Fm. The published experimental evidence is discussed in relation to configurationconstrained potential-energy-surface calculations, which suggest that the high-K isomers should be less susceptible to fission than their corresponding ground states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…The increased hindrance in fission of multi-qp states can be attributed to the reduced superfluity and increased fission barrier due to unpaired nucleons. In general, the fission barrier of a multi-qp state is higher and wider than that of the corresponding ground state in our configuration-constrained PES calculations [25,26,44,59]. It is found that the β 6 deformation contributes to the increased fission barrier height [26,59].…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…The increased hindrance in fission of multi-qp states can be attributed to the reduced superfluity and increased fission barrier due to unpaired nucleons. In general, the fission barrier of a multi-qp state is higher and wider than that of the corresponding ground state in our configuration-constrained PES calculations [25,26,44,59]. It is found that the β 6 deformation contributes to the increased fission barrier height [26,59].…”
mentioning
confidence: 57%
“…The shape is restricted to be axially symmetric due to the negligible triaxial deformations showing in the calculations with triaxiality [25,26,44]. The β 6 degree of freedom is included because of its important role in these nuclei such as the influence on the deformed shell gaps at N = 152 and Z = 100 [3,4], the K-isomer excitation energy [26], and the angular-momentum alignment in collective rotation [27].…”
mentioning
confidence: 99%
“…energies and fission barriers, but without inclusion of dynamical effects or the calculation of lifetimes [38,[144][145][146].…”
Section: Ground State Isomermentioning
confidence: 99%
“…By incorporating a dynamical treatment of pairing, SF of high-K states was found to depend critically on dynamically-induced superfluidity in the tunneling process [6]. Recently, the possibility that K isomers could be more stable in SHN has been discussed in terms of the shape of the fission barriers when using configuration constraints in calculations of the potential energies and fission barriers, but without inclusion of dynamical effects or the calculation of lifetimes [7,8]. State-of-the-art nuclear density functional theory calculations have underscored the importance of the interplay between pairing and shape parameters during the fission process [9].…”
mentioning
confidence: 99%